The Implementation Of The Rules Of Engagement For A Soldier: Defianus’s Case In Papua - Islami, Diajeng Dhea Annisa Aura (Veteran Law Review, 2024)
Indonesia is a legal state that possesses defense and security capabilities based on the regulations governing it. The main protector of the nation within it is the Indonesian National Military, whose duties and authorities are stipulated in Law Number 34 of 2004. However, there are often individuals who misuse their authority for their satisfaction. This research aims to address the relationship between the abuse of power in the case of Defianus Kogoya in Papua and the application of Rules of Engagement. This research utilizes the normative juridical research method with data sources including primary legal materials, such as the Constitution of the Republic of Indonesia, the National Defense Law, and legal materials from various relevant sources to support the analysis. The research findings indicate that, at the forefront of national defense, the Indonesian National Military must always be prepared to carry out its main role and function, which should be adjusted to threats and changes in political policies. Therefore, the Indonesian National Military need to be equipped with Rules of Engagement as limits in the use of force to remain controlled and not violate human rights, especially towards civilian populations not involved in the conflict.